2004
DOI: 10.1002/marc.200400030
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Crosslinkable Micropatterns by Amphiphilic Dendrimer Stamping

Abstract: Summary: Microcontact printing was used to deposit stable, nanostructured, amphiphilic and crosslinkable patterns of poly(amidoamine organosilicon) (PAMAMOS)‐dimethoxymethylsilyl (DMOMS) dendrimer multilayers onto silicon wafers, glass, and polyelectrolyte multilayers. The effects of dendrimer ink concentration, contact time, and inking method, on the thickness, uniformity, and stability of the resulting patterns were studied using optical microscopy, fluorescence microscopy, atomic force microscopy (AFM), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
(87 reference statements)
2
23
0
Order By: Relevance
“…Microcontact printing offers advantages over conventional photolithographic techniques because it is simple to perform and is not diffraction-limited. This technique has been used to make patterns of various small and large molecules on metals and silicon substrates [59][60][61][62], as well as to deposit proteins [63] and polyelectrolyte aggregates [64]. POPS is an approach that combines LBL assembly and µCP to generate alternating regions of different chemical functionalities on a surface by using graft, diblock copolymers or polyelectrolytes as ink [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Microcontact printing offers advantages over conventional photolithographic techniques because it is simple to perform and is not diffraction-limited. This technique has been used to make patterns of various small and large molecules on metals and silicon substrates [59][60][61][62], as well as to deposit proteins [63] and polyelectrolyte aggregates [64]. POPS is an approach that combines LBL assembly and µCP to generate alternating regions of different chemical functionalities on a surface by using graft, diblock copolymers or polyelectrolytes as ink [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Mark Worden and Ilsoon Lee of Michigan State University, 54 it was shown that PAMAMOS solutions are excellent inks for micropatterning using the well-known Harvard micro-stamping technique. 55 Considering the simplicity of this imaging technique and the possibilities of imparting conductivity or magnetism to the created patterns by encapsulating nanoscaled metallic particles into the deposited dendrimer molecules, this appears to be another attractive approach to microlithography.…”
Section: Electronics Photonics and Magneticsmentioning
confidence: 99%
“…Poly(dimethylsiloxane) (PDMS) stamps were first used to create patterns of thiols on gold [24], and silanes on silica [25]. Many other functional materials including m-d-poly(ethylene glycol) acid [26], polymers [27,28], polyelectrolyte aggregates [29] and dendrimers [30] have been patterned onto PEM coated substrates. LBL assembly on PDMS stamps and subsequent μCP was used to create 3D structures of PEM and bionanocomposite arrays with excellent selectivity [31,32].…”
Section: Introductionmentioning
confidence: 99%